2022
DOI: 10.1007/s11726-022-1351-3
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the mechanism of acupuncture intervention on pain emotion and pain cognition mediated by limbic system

Abstract: Pain is a complex physiological and psychological activity, involving at least three dimensions, including pain sensation, pain emotion, and pain cognition. Acupuncture can clearly relieve the pain sensation of patients and improve pain emotion and pain cognition induced by pain; acupuncture participates in the multi-dimensional regulation of pain through brain regions of the limbic system such as anterior cingulate cortex (ACC), amygdala (AMY), and hippocampus. By analyzing relevant literature, it has been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Acupuncture can modulate the emotional and motivational aspects of pain by influencing neural circuits within the limbic and reward systems, while also impacting the rewarding effects of pain. Recent studies have shed light on the role of the lateral hypothalamus (LH) in regulating neuropathic pain ( 43 ). The study found that LH neurons projecting from the lateral habenula (LHb) are involved in modulating neuropathic pain ( 44 ).…”
Section: Pain and Pain-related Anxietymentioning
confidence: 99%
“…Acupuncture can modulate the emotional and motivational aspects of pain by influencing neural circuits within the limbic and reward systems, while also impacting the rewarding effects of pain. Recent studies have shed light on the role of the lateral hypothalamus (LH) in regulating neuropathic pain ( 43 ). The study found that LH neurons projecting from the lateral habenula (LHb) are involved in modulating neuropathic pain ( 44 ).…”
Section: Pain and Pain-related Anxietymentioning
confidence: 99%